A framework for economic performance recovery in South Africa during the Corona Virus Disease 2019 (Covid-19) pandemic - Fotso, G. Bakam; Edoun, E. I.; Pradhan, A.; Sukdeo, N. (Technium Social Sciences Journal, 2022)
In the trajectory to protect people and ensure national security regarding the rapid spread of the Corona virus disease pandemic, restrictions measures adopted by the South African government have caused severe collateral damages to the local economy. This article aims to provide a framework for economic performance recovery while dealing with the pandemic consequences. Using primary and secondary data, the retrieved statistical model depicts that 96.90% of the COVID-19 Economic Performance Recovery’ behaviour depends on the movement of COVID-19 Banking revitalisation, COVID-19 Financial policies, COVID-19 Management Process, COVID-19 Stakeholders Involvement and COVID-19 Future perspectives since the correlation is very strong and positive with coefficients that are respectively 96.4%, 95.1%, 95.6% and 94.9%. The stakeholders’ involvement component was not significant with a p-value of .143 but its combination with other factors enhances economic performance recovery. The regression standardised residual for C19EPR with an asymmetric probability distribution characterised by a negative skewness of - .531 long left tail and the Kurtosis of -.977. For banking revitalisation, repo rate should be increased while banking regulations, loan guarantee scheme and the provisional mortgage forbearance to borrowers initiated with the pandemic should be suspended. Structural reforms should be implemented to sustain the implementation of the recovery plan namely the restructuration of trade policies and lowering barriers entry for business movements, supporting labour-intensive sectors like agriculture and tourism for inclusive growth and catalysing education and skills development. National and global pandemic -related stakeholders should be improved to support direct fiscal support and government guarantee schemes in addition to measures to provide liquidity to banks markets, alleviate US Dollar funding shortages. As part of the future perspectives to mitigate the pandemic issues, government should systematically monitor market price increase, and reduce exceptions for public policy considerations. In overall, recovery of economic performance in South Africa will depend on the GDP improvement and an increase of the repo rate. Furthermore, standard local issues like incessant trade disruptions, business declines, unemployment, drop of government revenues, orientated national funding and poverty increase should be improved as well. However, South African government only has to observe decentralised and implement international policies defined in the settings of the pandemic.